A Structural Equation Modelling Approach in Assessing the Sustainability of Indonesian Smallholder Oil Palm Farming - ., Kamaludin; Harisudin, Mohamad; Sutrisno, Joko; Irianto, Heru (Journal of Ecohumanism, 2024)
Oil palm plantations (Elaeis guineensis Jacq) in Indonesia have been considered as a leading sector to increase the country’s economic growth, create jobs, and improve the distribution of people’s income The production of oil palm fruit commodities in 2019 reached a total of 51,443,315 tonnes (Director General of Plantations, 2020). Its export volume in 2019 was 29,135,179 tonnes, equivalent to US 20,802,708,000. Oil palm crop production in Indonesia is managed by three groups: state-owned plantation companies, private plantation companies, and smallholder plantations. Oil palm plantation areas spanned 14,677,560 hectares in 2019, 41% of which were community-based plantations. These areas produced 14,846,112 tonnes of palm oil in the same year, accounting for 16% of the national palm oil crop production volume (Directorate General of Plantations, 2020). The development of oil palm plantation areas has made a major contribution to the country’s foreign exchange reserves, added to local revenue, encouraged the acceleration of economic development, and encouraged poverty alleviation in rural areas. This study aims to analyse the economic, social, environmental, institutional, and technological influences on the sustainability of independent oil palm farms in Sintang District. The research method used is the Structural Equation Model (SEM) operated through the AMOS programme. While the tools used in this study using a questionnaire with 216 respondents. From a total population of 491 respondents. The findings of this study indicate that the C.R value of the economic dimension is 4.026, social is 2.920, environmental is 3.237, institutional is 3.247, and technology is 2.694. This shows that there is a positive and significant relationship between the dimensions of the sustainability of independent oil palm farming.